Interactive theorem proving : 8th International Conference, ITP 2017, Brasília, Brazil, September 26-29, 2017, Proceedings /: 8th International Conference, ITP 2017, Brasília, Brazil, September 26-29, 2017, Proceedings. (2017) - Unknown
No abstract available